Enhancement of pullulanase production from recombinant Bacillus subtilis by optimization of feeding strategy and fermentation conditions - Zhang, Yu (AMB Express, 2020)
Pullulanase is an important starch-debranching enzyme mostly used in starch processing-related food industries. However, the levels of pullulanase produced from recombinant Bacillus subtilis, a Generally Recognized as Safe (GRAS) host, are generally limited. To enhance the activity of pullulanase, batch fermentation and fed-batch fermentation were systematically investigated. The overall purpose is to improve the fermentation yield by optimizing the feeding strategy in the fermentation process, thereby increasing the enzyme activity of pullulanase. Therefore, in this study, the feeding methods, the feeding ingredients, the feeding concentration, and pH values were studied in detail. The optimized fermentation conditions for pullulanase production from recombinant B. subtilis were determined as following: inoculum volume 7%, pH 6.5, the dissolved oxygen level 30%, and constant-rate feeding of 100 mL glucose solution (400 g L(−1)) in late logarithmic growth. The OD(600) of recombinant B. subtilis and enzyme activity were 84.54 and 102.75 U mL(−1), which were respectively 141% and 144% higher than that before optimization. These findings provided a prerequisite for further amplification of the fermentation system to obtain higher enzyme activity.